Narasi TV’s Action in Reputation Management due to Hacking Crisis - Amelia Pratiwi (Eduvest - Journal of Universal Studies, 2025)
Narasi TV, a digital television startup, was founded on September 6, 2017, by a dynamic trio of journalists: Najwa Shihab, Dahlia Citra, and Catharina Davy. This innovative platform is dedicated to delivering factual and participatory information, aiming to engage viewers in meaningful discourse. This article undertakes a detailed analysis of the crisis communication strategies employed by Narasi TV in the wake of a significant hacking attack that transpired in September 2022. Utilizing a qualitative research methodology, the study integrates the Situational Communication Theory (SCCT) to understand the nuances of their response. This research reveals that Narasi TV adeptly navigated the crisis, maintaining and enhancing its reputation through a commitment to transparent communication and fostering open dialogues with its audience about critical cybersecurity issues. In a strategic move to bolster its defenses, Narasi collaborated with Aliansi Jurnalis Independen (AJI) to secure legal advice and technical assistance, conducting thorough audits of their device security to mitigate the risk of future hacking incidents. Ultimately, it can be concluded that Narasi TV’s prompt of public trust was pivotal in reinforcing Narasi’s image as a credible source for information dissemination. This research sheds light on effective communication practices during a crisis. It provides valuable insights for other media organizations striving to manage their communication strategies in an ever-evolving digital landscape.